Numerical nonlinear analysis of RC beams with un-strengthened and CFRP-strengthened opening drilled under service loads within shear zones - Magdy Khalaf; Louay Aboul-Nour; Mahmoud Khater; Marwa Ibrahim (Fracture and Structural Integrity)
The current research deals with the Reinforced Concrete (RC) beams numerical modeling using the finite element analysis software ANSYS-standard and the proposed strengthening procedure if it is urgently required to drill rectangular or circular in shape openings within their shear zones under different applied service loads levels. The shear zone is selected to investigate drilling the opening within since it is a critical zone to reduce the structural section effective area against shear. The RC beams are analyzed under two concentrated loads till failure before and after applying the proposed opening strengthening technique by means of the Carbon Fibers Reinforced Polymer sheets (CFRP). The main aim of this research is simulating the real practice situation conditions where the RC beam is subjected to the service loads, supported temporary by means of hydraulic jacks, the opening is drilled and then the strengthening is performed after which the jacking supports are released. The used finite element modeling (FEM) is verified using one of the available experimental studies of FRP-strengthened simply supported beams with and without openings which found in the literature before achieving the investigation. The results of proposed numerical nonlinear modeling are introduced. Many aspects of structural analysis such as the initial cracking loads, load deflection curves, cracking patterns and failure loads and modes for the reference (solid without opening) and un-strengthened and strengthened opening main control and services loaded RC beams are introduced and analyzed in details. CFRP opening strengthening improved the beams structural behavior as a whole. The service loads up to about 40% of the ultimate design strength relatively have an unnoticeable influence on the strengthened opening RC beams bearing capacities regardless the opening shape. Some important conclusions and recommendations for designer and executive engineers are stated.